বাঙাল নাম - রায়চৌধুরী, তপন (কলকাতা : আনন্দ, 2007)
Autobiography of a professor, and social scientist from India, now resident of the United Kingdom.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Raychaudhuri, Tapan; College teachers -- India -- Biography; Social scientists -- India -- Biography; Education